Behavioral Specialization in Embodied Evolutionary Robotics: Why So Difficult? - Montanier, Jean-Marc; Carrignon, Simon; Bredeche, Nicolas (Frontiers in Robotics and AI, 2016)
Embodied evolutionary robotics is an on-line distributed learning method used in collective robotics where robots are facing open environments. This paper focuses on learning behavioural specialization, as defined by robots being able to demonstrate different kind of behaviours at the same time (e.g. division of labour). Using a foraging task with two resources available in limited quantities, we show that behavioural specialization is unlikely to evolve in the general case, unless very specific conditions are met regarding interactions between robots (a very sparse communication network is required) and the expected outcome of specialization (specialization into groups of similar sizes is easier to achieve). We also show that the population size (the larger the better) as well as the selection scheme used (favoring exploration over exploitation) both play important -- though not always mandatory -- roles. This research sheds light on why existing embodied evolution algorithms are limited with respect to learning efficient division of labour in the general case, ie. where it is not possible to guess before deployment if behavioural specialization is required or not, and gives directions to overcome current limitations.